PERSONAL CHARACTER DEVELOPMENT OF ACCOUNTING STUDENTS THROUGH CASE-BASED METHOD DURING THE COVID-19 PANDEMIC - Sri Rahayu; Netty Herwaty; R Rahayu (Universitas Brawijaya, 2022)
Primary Objective - to analyze the actions and experiences of accounting lecturers and students in online learning during the Covid-19 pandemic.Method - The study was action research. Data were collected through observation, discussion, documentation, and interviews. Research participants consisted of lecturers and students. Data analysis employed an interactive model.Primary Findings - Lecturers should be more creative and innovative in managing online classes. The personal characters developed include high participation, tolerance, respect for differences, independence, and thinking fast and critically. Theory and Policy Implications – This research contributes to the development of accounting education. Universities and faculties can make the case-based method an alternative for technical accounting courses.The research novelty is implementing the case-based method in online accounting education.